(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
This Project gives the information about to design and fabrication of injection Molding die for Production of washer by using Plastic material. For Increasing the Production rate,designing and manufacturing the multi cavity die and also using HDPE (High Density Polyethylene)to overcome the existing plastic material drawbacks.The injection molding die contains the core plate,top and bottom supported plates, channels or runners, sprue, vents ejector and its pins and horn pins,etc. The Greek word of “plastic’’meaning is ‘able to be shaped and molded’, in so many different plastic materials I am using High Density Polyethylene material for production of plastic washer components.